2014
DOI: 10.1128/aem.04283-13
|View full text |Cite
|
Sign up to set email alerts
|

In-Feed Use of Heavy Metal Micronutrients in U.S. Swine Production Systems and Its Role in Persistence of Multidrug-Resistant Salmonellae

Abstract: The study aimed to characterize the role of heavy metal micronutrients in swine feed in emergence of heavy-metal-tolerant and multidrug-resistant Salmonella organisms. We conducted a longitudinal study in 36 swine barns over a 2-year period. The feed and fecal levels of Cu 2؉ and Zn 2؉ were measured. Salmonella was isolated at early and late finishing. MICs of copper sulfate and zinc chloride were measured using agar dilution. Antimicrobial susceptibility was tested using the Kirby-Bauer method, and 283 isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 50 publications
4
63
0
Order By: Relevance
“…Concentration of heavy metals in pig intestines may represent substantial selective pressure contributing to the success of this clone. Indeed, a recent study reported that an enhanced MIC (20–24 mmol/L) compared with the baseline MIC (16 mmol/L) for copper sulfate was significantly more likely to be found in isolates from pig feces ( 30 ). …”
Section: Discussionmentioning
confidence: 99%
“…Concentration of heavy metals in pig intestines may represent substantial selective pressure contributing to the success of this clone. Indeed, a recent study reported that an enhanced MIC (20–24 mmol/L) compared with the baseline MIC (16 mmol/L) for copper sulfate was significantly more likely to be found in isolates from pig feces ( 30 ). …”
Section: Discussionmentioning
confidence: 99%
“…Switzerland). It should also be taken into account that some negative characteristics due to the burden on the environment by excretion and to potential selection for specific antimicrobial resistance have been described in literature as well (Mavromichalis, 2011;Medardus et al, 2014) and might have influenced the opinion of the respondents. Furthermore some authors describe only partial effect of zinc oxide or only for a short period, leading to a less positive evaluation (Janczyk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms employed by bacteria to protect against Zn include reducing absorption, increasing efficiency of efflux, transformation of toxic forms to low toxicity and internal isolation, some of which might cause resistance to antibiotics. There is compelling support for the notion that exposure to heavy metals can act as an indirect selective pressure for maintaining antibiotic resistance (Cesare, Eckert, & Corno, ; Hu, Wang, Li, Li, et al., ; Medardus et al., ). The co‐selection of heavy metal and ARGs in various ecological conditions, such as waters, sediments and soils, which increase the complexity of the ecological role of ARGs, and debases the effectiveness of prevention and control actions, has also been postulated to be an important element for the spread and persistence of ARGs (Hu, Wang, Li, Li, et al., ; Hu, Wang, Li, Shi, et al., ; Peltier et al., ; Seiler & Berendonk, ).…”
Section: Discussionmentioning
confidence: 99%